Method development for the cyclic characterization of thin copper layers for PCB applications. Issue 2 (29th April 2014) - Fellner, K.; Fuchs, P.F.; Pinter, G.; Antretter, T.; Krivec, T.
Abstract : Purpose: – The overall aim of this research work was the improvement of the failure behavior of printed circuit boards (PCBs). In order to describe the mechanical behavior of PCBs under cyclic thermal loads, thin copper layers were characterized. The mechanical properties of these copper layers were determined in cyclic four-point bend tests and in cyclic tensile-compression tests, as their behavior under changing tensile and compression loads needed to be evaluated. Design/methodology/approach: – Specimens for the four-point bend tests were manufactured by bonding 18- μ m-thick copper layers on both sides of 10-mm-thick silicone plates. The silicone was characterized in tensile, shear and blow-up tests to provide input data for a hyperelastic material model. Specimens for the cyclic tensile-compression tests were produced in a compression molding process. Four layers of glass fiber-reinforced epoxy resin (thickness 90 μ m) and five layers of copper (thickness 60 μ m) were applied. Findings: – The results showed that, due to the hyperelastic material behavior of silicone, the four-point bend tests were applicable only for small strains, while the cyclic tensile-compression tests could successfully be applied to characterize thin copper foils in tensile and compression up to 1 percent strain. Originality/value: – Thin copper layers (foils) could be characterized successfully under cyclic tensile and compression loads.